Analysis of Muslim Consumption Behavior During Ramadan in the Perspective of Maqashid Shariah (A Study of Muslims in Indonesia) - Shibghatallah; Abdul Wadud Nafis (Journal of Islamic Economics Perspectives, 2026)
Ramadan, the holy month for Muslims, is spiritually intended to foster piety through self-restraint, including controlling desires and excessive consumption. However, empirical reality in various parts of the world, including Indonesia, reveals a paradoxical phenomenon: a significant surge in household consumption during this month. This research aims to analyze the consumption behavior of Muslims during Ramadan, both globally and in Indonesia, and evaluate it using the framework of Maqashid Shariah (the objectives of Islamic law). The research method employs a qualitative-descriptive approach with library research, integrating secondary data from market research institute reports, statistical agencies, and relevant academic literature. The findings indicate a significant increase in the consumption of food, beverages, and other symbolic activities during Ramadan, which in some cases leads to israf (excessiveness) and tabdzir (wastefulness). The Maqashid Shariah analysis reveals that this behavior poses challenges to the preservation of wealth (hifz al-mal), life (hifz al-nafs), and even spirituality (hifz al-din) itself. The theoretical implication of this research is the strengthening of the Islamic consumption concept, which is not only based on fulfilling material needs but also on spiritual and social maslahah (benefit). Practically, this research recommends the need for public education and economic policies that encourage a moderate Ramadan consumption pattern aligned with maqashid shariah.